Financial Inclusion and Threshold Effects in Carbon Emissions - Nidhaleddine Ben Cheikh; Christophe Rault (Institute of Labor Economics (IZA), 2024)
While the financial inclusion would induce greater pollutant emissions through its impact of economic activity, the increased access to financial services may unleash investments in green technologies. This papier investigates whether the financial inclusion influences the dynamic of carbon dioxide (CO2) emissions in a sample of 70 countries during the last decade. We implement panel threshold techniques to explore the possible regime shifts in the environmental quality. Our results reveal that an increased financial access impacts air pollution depending on the level of economic development. While financial inclusion would increase CO2 emissions under lower-income regimes, the environment quality seems to be enhanced with more inclusiveness at later stages of development. Sounder environmental policies are needed for less developed countries to align financial inclusion initiatives with sustainable economic development.
Keywords: C23; O16; O44; Q53; Q56; 330; financial inclusion; carbon emissions; panel threshold modelling